Pengambilan Keputusan dalam Al-Qur’an dan Al-Hadits (Upaya Menentukan Kebijakan Pendidikan Secara Religius) - Ahmad Fahrudin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
Islamic education received a lot of criticism from various groups both from the practice of education in general, but all parties agreed, both from the stakeholders' stakeholders, that the education of a nation would determine the destiny of the nation and the nation going forward. Because this is what will determine and contribute to education and culture in the future. A very well-known theory, namely the theory of life choices (real life choices) teaches that, humans throughout their lives always make choices in accordance with the circumstances they experienced. Take alternative choices if possible can be used in appropriate conditions, so that they can be used as well as possible. As education practitioners in the level of Islamic teachings, it is important to base a decision on the two best guidelines, namely the Qur'an and Hadith, this article will discuss decision making in the Qur'an and Hadith. Conclusion from paper are: 1) Decision making is an action of a leader in taking the most accurate alternative according to some alternative choices in front of him. 2) The role of a leader is very important for decision making in any situation and condition, so that it can lead to a better direction in an organization 3) Priority that must be prioritized for a leader towards decision making is the principle of the interests of the people above the interests of themselves or groups. 4) In decision making, it should be based on the teachings in the Qur'an and Hadith. A part from the value of “kebarokahan” obtained from him.